(untitled) (Andamios, Revista de Investigación Social, 2009)
Research, mainly that involving human beings, in many circumstances is associated to risk, even peril, specially when abuses affecting fundamental rights of persons like life or integrity are progressively discovered. In this paper we analyze the context which favors the fact that regulations and controls over research protocols allow violation of Human Rights. The bioethical reference framework is the human rights declarations made by UN in relation to the Declaration of Helsinki, regarded as the standard with widest procedural acceptance and moral credibility in the history of international standards in the field of research.